GAYA BAHASA METAFOR DALAM AL-QUR’AN - Muzakki, Akhmad (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2009)
Language is a category for referring to a particular object. It represents reality, not the reality itself. Therefore, language is basically partial, does not represent something completely. For that reason, it is difficult for us to name a certain object because not all of languages provide them. In our empirical world, it is difficult to select an appropriate language to represent reality. Moreover, Koran language emphasize the aspect of belief and understanding. So, in the effort to overcome the language stagnancy, it is very realistic to find out metaphorical and analogous language in Koran. It is due to the fact that metaphor and analogy can bridge the limited human ratio and the unlimited Koran.